The effect of Aflatoxin B1 on tumor-related genes and phenotypic characters of MCF7 and MCF10A cells - Ahmed Adam, Mowaffaq Adam; Muhd Kamal, Laina Zarisa; Kanakal, Mahibub; Babu, Dinesh; Dahham, Saad Sabbar; Tabana, Yasser; Lok, Bronwyn; Bermoy, Brittany M.; Yunus, Muhammad Amir; Than, Leslie Thian Lung; Barakat, Khaled; Sandai, Doblin (Multidisciplinary Digital Publishing Institute, 2022)
The fungal toxin aflatoxin B1 (AB1) and its reactive intermediate, aflatoxin B1-8, 9 epoxide, could cause liver cancer by inducing DNA adducts. AB1 exposure can induce changes in the expression of several cancer-related genes. In this study, the effect of AB1 exposure on breast cancer MCF7 and normal breast MCF10A cell lines at the phenotypic and epigenetic levels was investigated to evaluate its potential in increasing the risk of breast cancer development. We hypothesized that, even at low concentrations, AB1 can cause changes in the expression of important genes involved in four pathways, i.e., p53, cancer, cell cycle, and apoptosis. The transcriptomic levels of BRCA1, BRCA2, p53, HER1, HER2, cMyc, BCL2, MCL1, CCND1, WNT3A, MAPK1, MAPK3, DAPK1, Casp8, and Casp9 were determined in MCF7 and MCF10A cells. Our results illustrate that treating both cells with AB1 induced cytotoxicity and apoptosis with reduction in cell viability in a concentration-dependent manner. Additionally, AB1 reduced reactive oxygen species levels. Phenotypically, AB1 caused cell-cycle arrest at G1, hypertrophy, and increased cell migration rates. There were changes in the expression levels of several tumor-related genes, which are known to contribute to activating cancer pathways. The effects of AB1 on the phenotype and epigenetics of both MCF7 and MCF10A cells associated with cancer development observed in this study suggest that AB1 is a potential risk factor for developing breast cancer.